Soil-Transmitted Helminths in Southwestern China: A Cross-Sectional Study of Links to Cognitive Ability, Nutrition, and School Performance among Children. - Chengfang Liu; Renfu Luo; Hongmei Yi; Linxiu Zhang; Shaoping Li; Yunli Bai; Alexis Medina; Scott Rozelle; Scott Smith; Guofei Wang; Jujun Wang (Public Library of Science (PLoS), 2015)
Empirical evidence suggests that the prevalence of soil-transmitted helminth (STH) infections in remote and poor rural areas is still high among children, the most vulnerable to infection. There is concern that STH infections may detrimentally affect children's healthy development, including their cognitive ability, nutritional status, and school performance. Medical studies have not yet identified the exact nature of the impact STH infections have on children. The objective of this study is to examine the relationship between STH infections and developmental outcomes among a primary school-aged population in rural China.We conducted a large-scale survey in Guizhou province in southwest China in May 2013. A total of 2,179 children aged 9-11 years living in seven nationally-designated poverty counties in rural China served as our study sample. Overall, 42 percent of the sample's elementary school-aged children were infected with one or more of the three types of STH--Ascaris lumbricoides (ascaris), Trichuris trichuria (whipworm) and the hookworms Ancylostoma duodenale or Necator americanus. After controlling for socioeconomic status, we observed that infection with one or more STHs is associated with worse cognitive ability, worse nutritional status, and worse school performance than no infection. This study also presents evidence that children with Trichuris infection, either infection with Trichuris only or co-infected with Trichuris and Ascaris, experience worse cognitive, nutritional and schooling outcomes than their uninfected peers or children infected with only Ascaris.We find that STH infection still poses a significant health challenge among children living in poor, rural, ethnic areas of southwest China. Given the important linkages we find between STH infection and a number of important child health and educational outcomes, we believe that our results will contribute positively to the debate surrounding the recent Cochrane report.